Answer:
y + 1/2 = 3(x - 2)
Step-by-step explanation:
We have to think about this question in point-slope form, which is a form that explicitly gives us the slope of the line and a single point that it passes through. Point-slope form looks like this: y - y1 = m(x - x1), where m is the slope and (x1,y1) is a point that the line goes through. We are given that the line goes through (2, -1/2) which means x1 = 2 and y1 = (-1/2). We are also given that the slope is 3. We can plug these quantities into the equation to solve:
y - (-1/2) = 3(x - 2) OR y + 1/2 = 3(x - 2)